Development of Guided Discovery Learning to Improve Reflective Thinking - Ignasius Fandy Jayanto; Sri Hastuti Noer; Caswita Caswita (SAINTIS Publishing, 2019)
This study is a development research that aims (a) to produce valid and practical Guided Discovery learning to improve the ability of reflective thinking, and (b) to determine the effectiveness of Guided Discovery learning to improve the ability to think reflective. This research is a Research and Development (R D). The research subjects were seventh grade students of SMP Paramarta 1 Seputih Banyak in the academic yearof 2018 / 2019. The instruments used are observation sheets, interview sheets, validity assessment instruments, trial sheets, and reflective thinking test instruments. The results of this study are (a) Guided Discovery learning has valid and practical criteria and (b) Average N-Gain scores mathematically reflective thinking of students after given Guided Discovery learning bigger than the average N-Gain score of mathematical reflective thinking skills of students who following conventional learning. Suggestions for developing Guided Discovery learning as an alternative to improve the ability of mathematical reflective thinking in junior high school students.